ANALYSIS OF REGIONAL REVENUE AND EXPENDITURE BUDGET PERFORMANCE BEFORE AND DURING THE COVID-19 PANDEMIC IN THE MAGELANG REGENCY GOVERNMENT FOR THE 2019-2020 PERIOD - Nadilla Amanda Raissa; Ari Nurul Fatimah (Transpublika Publisher, 2022)
This study analyzes the Financial Performance of the Magelang Regency Government before the pandemic and during the COVID-19 pandemic by analyzing the level of regional independence, the effectiveness ratio of regional original income, the regional financial efficiency ratio, and the compatibility ratio. In this study, the data used is the Budget Realization Report for the 2019 and 2020 fiscal years. The method used in this research is to use quantitative descriptive which aims to explain information and descriptions of the development of financial performance as reflected in the Magelang Regency APBD before the pandemic and at the time of the pandemic occurs. Based on the research results, Magelang Regency regional financial independence ratio from 2019-2020 is classified as very low. Meanwhile, PAD effectiveness ratio of Magelang Regency from 2019 to 2002 shows good financial performance and is classified as very effective, followed by financial efficiency ratio in 2019 to 2020 shows an efficient performance. Thus, the Magelang district compatibility ratio from 2019 to 2020 has decreased, this is due to the diversion of the allocation of funds for handling COVID-19.